New insights into plant development in New England. - Dolan, L; Langdale, J (2004)
This year, the biannually organized FASEB meeting 'Mechanisms in Plant Development' took place in August in Vermont, USA, organized by Martin Hulskamp (University of Koln, Koln, Germany) and John Schiefelbein (University of Michigan, Ann Arbor, MI, USA). The meeting covered numerous topics, ranging from patterning and differentiation to the evolution of developmental mechanisms. Despite apparent distinctions between the sessions, many of the talks were broad ranging and most highlighted unifying developmental concepts.